Seroprevalence of CMV and HSV in Kidney Transplant Donor Candidates and Recipients at Ngoerah Hospital, Denpasar - Trisnawati, Ni Nyoman Ayu; Somia, I Ketut Agus; Kandarini, Yenny (Indonesian Journal of Kidney and Hypertension, 2026)
Background: Despite significant advancements in solid organ transplantation over recent decades, infections remain a leading cause of morbidity and mortality among transplant recipients. Herpesviruses, particularly Cytomegalovirus (CMV) and Herpes Simplex Virus (HSV), are the most common viral pathogens affecting this patient population. This study aims to evaluate the seroprevalence of CMV and HSV infections among kidney transplant donor and recipient candidates at RS. Ngoerah Denpasar. Methods: This descriptive study involved 66 adult subjects, comprising 33 kidney transplant donor candidates and 33 recipient candidates, all aged over 18 years. The study participants were evaluated for CMV and HSV seroprevalence using serological tests, including IgG and IgM antibodies, to determine the presence of latent or active infections. The study population included patients with chronic kidney disease (CKD) stage V who were candidates for kidney transplantation. Results: Among the 33 donor candidates, 39.4% were found to have both CMV and HSV infections, with 45.5% testing positive for IgG anti-CMV, indicating a latent CMV infection. In the recipient candidate group, 27.3% were infected with both CMV and HSV, with 42.4% showing seropositivity for IgG anti-CMV. Additionally, a small proportion of donor and recipient candidates were found to have reactivated HSV infections, as indicated by the presence of IgM antibodies. The study highlights the significant prevalence of CMV and HSV infections among kidney transplant donor and recipient candidates. Conclusion: These findings underscore the importance of thorough serological screening prior to transplantation to identify latent infections that may influence post-transplant outcomes.